Seeing Students Learn Science: Integrating Assessment and Instruction in the Classroom - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Science educators in the United States are adapting to a new vision of how students learn science. Children are natural explorers and their observations and intuitions about the world around them are the foundation for science learning. Unfortunately, the way science has been taught in the United States has not always taken advantage of those attributes. Some students who successfully complete their K–12 science classes have not really had the chance to "do" science for themselves in ways that harness their natural curiosity and understanding of the world around them.
Keywords: Education

Call to Action for Science Education: Building Opportunity for the Future - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Scientific thinking and understanding are essential for all people navigating the world, not just for scientists and other science, technology, engineering and mathematics (STEM) professionals. Knowledge of science and the practice of scientific thinking are essential components of a fully functioning democracy. Science is also crucial for the future STEM workforce and the pursuit of living wage jobs. Yet, science education is not the national priority it needs to be, and states and local communities are not yet delivering high quality, rigorous learning experiences in equal measure to all students from elementary school through higher education. Call to Action for Science Education: Building Opportunity for the Future articulates a vision for high quality science education, describes the gaps in opportunity that currently exist for many students, and outlines key priorities that need to be addressed in order to advance better, more equitable science education across grades K-16. This report makes recommendations for state and federal policy makers on ways to support equitable, productive pathways for all students to thrive and have opportunities to pursue careers that build on scientific skills and concepts. Call to Action for Science Education challenges the policy-making community at state and federal levels to acknowledge the importance of science, make science education a core national priority, and empower and give local communities the resources they must have to deliver a better, more equitable science education.
Keywords: Education

English Learners in STEM Subjects: Transforming Classrooms, Schools, and Lives - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The imperative that all students, including English learners (ELs), achieve high academic standards and have opportunities to participate in science, technology, engineering, and mathematics (STEM) learning has become even more urgent and complex given shifts in science and mathematics standards. As a group, these students are underrepresented in STEM fields in college and in the workforce at a time when the demand for workers and professionals in STEM fields is unmet and increasing. However, English learners bring a wealth of resources to STEM learning, including knowledge and interest in STEM-related content that is born out of their experiences in their homes and communities, home languages, variation in discourse practices, and, in some cases, experiences with schooling in other countries.
Keywords: Education

Science Teachers' Learning: Enhancing Opportunities, Creating Supportive Contexts - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
Currently, many states are adopting the Next Generation Science Standards (NGSS) or are revising their own state standards in ways that reflect the NGSS. For students and schools, the implementation of any science standards rests with teachers. For those teachers, an evolving understanding about how best to teach science represents a significant transition in the way science is currently taught in most classrooms and it will require most science teachers to change how they teach. That change will require learning opportunities for teachers that reinforce and expand their knowledge of the major ideas and concepts in science, their familiarity with a range of instructional strategies, and the skills to implement those strategies in the classroom. Providing these kinds of learning opportunities in turn will require profound changes to current approaches to supporting teachers' learning across their careers, from their initial training to continuing professional development. A teacher's capability to improve students' scientific understanding is heavily influenced by the school and district in which they work, the community in which the school is located, and the larger professional communities to which they belong. Science Teachers' Learning provides guidance for schools and districts on how best to support teachers' learning and how to implement successful programs for professional development. This report makes actionable recommendations for science teachers' learning that take a broad view of what is known about science education, how and when teachers learn, and education policies that directly and indirectly shape what teachers are able to learn and teach. The challenge of developing the expertise teachers need to implement the NGSS presents an opportunity to rethink professional learning for science teachers. Science Teachers' Learning will be a valuable resource for classrooms, departments, schools, districts, and professional organizations as they move to new ways to teach science.
Keywords: Education

A Framework for K-12 Science Education: Practices, Crosscutting Concepts, and Core Ideas - National Research Council (The National Academies Press, 2012)
Science, engineering, and technology permeate nearly every facet of modern life and hold the key to solving many of humanity's most pressing current and future challenges. The United States' position in the global economy is declining, in part because U.S. workers lack fundamental knowledge in these fields. To address the critical issues of U.S. competitiveness and to better prepare the workforce, A Framework for K-12 Science Education proposes a new approach to K-12 science education that will capture students' interest and provide them with the necessary foundational knowledge in the field.
Keywords: Education

Guide to Implementing the Next Generation Science Standards - National Research Council (The National Academies Press, 2015)
A Framework for K-12 Science Education and Next Generation Science Standards (NGSS) describe a new vision for science learning and teaching that is catalyzing improvements in science classrooms across the United States. Achieving this new vision will require time, resources, and ongoing commitment from state, district, and school leaders, as well as classroom teachers. Successful implementation of the NGSS will ensure that all K-12 students have high-quality opportunities to learn science. Guide to Implementing the Next Generation Science Standards provides guidance to district and school leaders and teachers charged with developing a plan and implementing the NGSS as they change their curriculum, instruction, professional learning, policies, and assessment to align with the new standards. For each of these elements, this report lays out recommendations for action around key issues and cautions about potential pitfalls. Coordinating changes in these aspects of the education system is challenging. As a foundation for that process, Guide to Implementing the Next Generation Science Standards identifies some overarching principles that should guide the planning and implementation process. The new standards present a vision of science and engineering learning designed to bring these subjects alive for all students, emphasizing the satisfaction of pursuing compelling questions and the joy of discovery and invention. Achieving this vision in all science classrooms will be a major undertaking and will require changes to many aspects of science education. Guide to Implementing the Next Generation Science Standards will be a valuable resource for states, districts, and schools charged with planning and implementing changes, to help them achieve the goal of teaching science for the 21st century.
Keywords: Education

Developing Assessments for the Next Generation Science Standards - National Research Council (The National Academies Press, 2014)
Assessments, understood as tools for tracking what and how well students have learned, play a critical role in the classroom. Developing Assessments for the Next Generation Science Standards develops an approach to science assessment to meet the vision of science education for the future as it has been elaborated in A Framework for K-12 Science Education (Framework) and Next Generation Science Standards (NGSS). These documents are brand new and the changes they call for are barely under way, but the new assessments will be needed as soon as states and districts begin the process of implementing the NGSS and changing their approach to science education. The new Framework and the NGSS are designed to guide educators in significantly altering the way K-12 science is taught. The Framework is aimed at making science education more closely resemble the way scientists actually work and think, and making instruction reflect research on learning that demonstrates the importance of building coherent understandings over time. It structures science education around three dimensions - the practices through which scientists and engineers do their work, the key crosscutting concepts that cut across disciplines, and the core ideas of the disciplines - and argues that they should be interwoven in every aspect of science education, building in sophistication as students progress through grades K-12. Developing Assessments for the Next Generation Science Standards recommends strategies for developing assessments that yield valid measures of student proficiency in science as described in the new Framework. This report reviews recent and current work in science assessment to determine which aspects of the Framework's vision can be assessed with available techniques and what additional research and development will be needed to support an assessment system that fully meets that vision. The report offers a systems approach to science assessment, in which a range of assessment strategies are designed to answer different kinds of questions with appropriate degrees of specificity and provide results that complement one another. Developing Assessments for the Next Generation Science Standards makes the case that a science assessment system that meets the Framework's vision should consist of assessments designed to support classroom instruction, assessments designed to monitor science learning on a broader scale, and indicators designed to track opportunity to learn. New standards for science education make clear that new modes of assessment designed to measure the integrated learning they promote are essential. The recommendations of this report will be key to making sure that the dramatic changes in curriculum and instruction signaled by Framework and the NGSS reduce inequities in science education and raise the level of science education for all students.
Keywords: Education

Science and Engineering for Grades 6-12: Investigation and Design at the Center - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
It is essential for today's students to learn about science and engineering in order to make sense of the world around them and participate as informed members of a democratic society. The skills and ways of thinking that are developed and honed through engaging in scientific and engineering endeavors can be used to engage with evidence in making personal decisions, to participate responsibly in civic life, and to improve and maintain the health of the environment, as well as to prepare for careers that use science and technology.
Keywords: Education